2016
DOI: 10.1371/journal.pgen.1006071
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Structural Variation on Chromosome 27 Leads to the Ectopic Expression of HOXB8 and the Muffs and Beard Phenotype in Chickens

Abstract: Muffs and beard (Mb) is a phenotype in chickens where groups of elongated feathers gather from both sides of the face (muffs) and below the beak (beard). It is an autosomal, incomplete dominant phenotype encoded by the Muffs and beard (Mb) locus. Here we use genome-wide association (GWA) analysis, linkage analysis, Identity-by-Descent (IBD) mapping, array-CGH, genome re-sequencing and expression analysis to show that the Mb allele causing the Mb phenotype is a derived allele where a complex structural variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 72 publications
0
48
0
Order By: Relevance
“…Although the evolution of enhancers de novo from mutations in non-functional sequences represents an obvious null hypothesis (Figure 1B), this mechanism has been difficult to study, and it more often turns out that new regulatory sequences have evolved from pre-existing ancestral ones. Studies of the domesticated chicken have shown how large-scale chromosome rearrangements and structural variations have contributed to diverse phenotypes by rearranging or duplicating regulatory elements and placing them in association with new genes (“promoter switching” in Figure 1B) [1214]. Multiple studies have shown how novel expression domains can evolve from pre-existing enhancers that derive additional tissue specificities (“co-option” in Figure 1B) [1518].…”
Section: How To Build a New Enhancermentioning
confidence: 99%
“…Although the evolution of enhancers de novo from mutations in non-functional sequences represents an obvious null hypothesis (Figure 1B), this mechanism has been difficult to study, and it more often turns out that new regulatory sequences have evolved from pre-existing ancestral ones. Studies of the domesticated chicken have shown how large-scale chromosome rearrangements and structural variations have contributed to diverse phenotypes by rearranging or duplicating regulatory elements and placing them in association with new genes (“promoter switching” in Figure 1B) [1214]. Multiple studies have shown how novel expression domains can evolve from pre-existing enhancers that derive additional tissue specificities (“co-option” in Figure 1B) [1518].…”
Section: How To Build a New Enhancermentioning
confidence: 99%
“…Consistent with these findings, genetic crosses and genomic mapping approaches implicate the mesodermally-expressed transcription factors PITX1 and TBX5 in feather-footed domestic pigeons and chickens (Domyan et al, 2016). The head crests of certain chicken breeds probably result from a re-specification of cranial to dorsal body skin identity, and this phenotype is linked to ectopic expression of HOXC8 , a mesodermally-expressed transcription factor (Kanzler et al, 1997; Wang et al, 2012) ( HOXB8 , which is linked to the muffs and beard phenotype in chickens, is expressed in both mesodermal and ectodermal skin derivatives; Guo et al, 2016; Hughes et al, 2011). However, the pigeon head crest maps to EPHB2 , which is expressed throughout the skin mesenchyme and at the mesenchymal-epithelial interface (Suksaweang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The Muffs and beard (Mb) trait is found in a variety of chicken breeds and is characterized by small tufts of elongated feathers that surround the face and beak (Bartels, 2003; Guo et al, 2016). By combining genetic mapping, genomic association tests, and IBD analyses, Guo et al (2016) identified a 48-kb region as the Mb candidate locus.…”
Section: Variation In Epidermal Appendage Structurementioning
confidence: 99%
See 2 more Smart Citations